The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1981
DOI: 10.1083/jcb.91.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphogenesis in wild-type and fertilization-defective mutants of Caenorhabditis elegans.

Abstract: Taking advantage of conditions that allow spermatogenesis in vitro, the timing and sequence of morphological changes leading from the primary spermatocyte to the spermatozoon is described by light and electron microscopy . Together with previous studies, this allows a detailed description of the nuclear, cytoplasmic, and membrane changes occurring during spermatozoan morphogenesis . By comparison with wild type, abnormalities in spermatogenesis leading to aberrant infertile spermatozoa are found in six fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
225
0
3

Year Published

1982
1982
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 196 publications
(236 citation statements)
references
References 32 publications
8
225
0
3
Order By: Relevance
“…The morphological defects in sperm of both strains are the same: the pseudopods are shorter than normal and MO's do not fuse with the surface membrane (29). Although short, these pseudopods bear pseudopodial projections that undergo the same movements as those on wild-type cells (19).…”
Section: Movement Of Latex Beads During Spermiogenesismentioning
confidence: 64%
See 3 more Smart Citations
“…The morphological defects in sperm of both strains are the same: the pseudopods are shorter than normal and MO's do not fuse with the surface membrane (29). Although short, these pseudopods bear pseudopodial projections that undergo the same movements as those on wild-type cells (19).…”
Section: Movement Of Latex Beads During Spermiogenesismentioning
confidence: 64%
“…Activating spermatozoa were recognized by several morphological criteria : few fused MO's, incomplete accumulation of cytoplasmic laminar membranes at the pseudopod-cell-body junction and short pseudopods without projections (18,29) . Electron micrographs of these immature spermatozoa revealed a near uniform distribution of ferritin on the surface of both the cell body and the pseudopod (Fig.…”
Section: Fate Of Surface Lectin Receptors During Spermiogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…60 and references therein). Or perhaps there are other proteins not yet identified that create a novel cytoplasmic structure, such as the major sperm protein of nematode sperm (61) , which appears to be entirely different from actin, yet plays a very similar function in the motility of these migratory sperm (62) .…”
Section: Other Ways To Structure the Cytoplasmmentioning
confidence: 99%